2021
DOI: 10.1002/hep4.1802
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Mortality Among Patients With NAFLD Hospitalized With COVID‐19 Infection

Abstract: is the guarantor of this work and had full access to all the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. All authors read and approved the final version of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
1
46
1
1
Order By: Relevance
“…When we analyzed clinical outcomes, we found a mortality rate of 13% within 60 days from the admission to the emergency department. This finding is slightly higher than the 10.9% reported in the study by Li Y. et al [ 18 ] and 10.8% in the study by Younossi et al [ 15 ]. Of note, we found a higher prevalence of increased FIB-4 in patients who died compared to survivors.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…When we analyzed clinical outcomes, we found a mortality rate of 13% within 60 days from the admission to the emergency department. This finding is slightly higher than the 10.9% reported in the study by Li Y. et al [ 18 ] and 10.8% in the study by Younossi et al [ 15 ]. Of note, we found a higher prevalence of increased FIB-4 in patients who died compared to survivors.…”
Section: Discussioncontrasting
confidence: 62%
“…This figure is similar to that reported in a smaller cohort of 202 COVID-19 patients in which the prevalence of FIB-4 > 2.67 was 31.2% [ 18 ]. In addition, in a study using a FIB-4 cut off > 2.91 the prevalence of high FIB-4 was 24.9% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with the recent findings, which reported worse outcomes in COVID-19 patients with preexisting chronic liver diseases [ 45 ]. For example, FIB-4 was found to be an independent factor of mortality among hospitalized COVID-19 patients with imaging- or liver biopsy-proven NAFLD [ 46 ]. Sachdeva et al found that the NFLAD was a strong predictor for mortality in patients infected with SARS-CoV-2 [ 13 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“… 126 Non-alcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH) are features of lipodystrophy 120 , 126 and within this pathogenesis, 122 , 123 lipodystrophy may increase the risk of complications in COVID-19. 127 , 128 …”
Section: Underweightmentioning
confidence: 99%